ANATOMICAL VARIANTS OF PYRIFORM APERTURES AND NASAL BONES IN PATIENTS WITH NORMAL CONFIGURATION AND DIFFERENT AESTHETIC DEFORMITIES OF EXTERNAL NOSE USING MULTISLICE COMPUTED TOMOGRAPHY - D. A. Lezhnev; D. V. Davydov; M. O. Dutova; V. V. Petrovskaya (Вестник рентгенологии и радиологии)
Objective. To identify the anatomical variants of nasal bones and pyriform apertures in view of normal configuration of external nose and different types of aesthetic nasal deformities, to estimate its possible relations.Material and methods. We performed a retrospective analysis of multi-slice computed tomography (MSCT) data of 2737 patients with the image processing (multiplanar and 3D-volume rendering). The sample comprised 121 patients with aesthetic nasal deformities (rhinokyphosis – nasal hump, long nose, combined deformity like a hidden hump, short nose, wide nose) and 37 individuals with normal European nasal configuration.Results. The most frequent variants of pyriform apertures are drop, heart and pear types. The most common variants of nasal bones in all groups were II, V, VI types according to Lang and Baumeister. Every kind of deformities was described with their characteristic features of pyriform apertures and nasal bones.Conclusion. Statistically proved correlation between the facts of deformities and variants of pyriform apertures and nasal bones was obtained. The preoperative study of variable anatomy must be always performed for improving functional and aesthetic results of rhinoplasty.